Eucharystia u Homera? - Piasecki, Dariusz (Vox Patrum, 2018)
The article attempts to answer the question: is it possible to represent the Last Supper of Jesus and His Apostles by means of verses selected from Homer’s Iliad and the Odyssey. The Homeric Cento no. 40, which emphasizes the community of Christ’s table with His disciples, has been a subject of my analysis. The specific selection of Homeric verses, with some minor modifications, allowed the centonist to construct a new text with a completely different context and content, reflecting both the reality of the Upper Room and the establishment of the Eucharist by Jesus.